Systematic Literature Review : Analisis Metode Simpleks dalam Menyelesaikan Permasalahan dalam Kehidupan Sehari-Hari - Ghasani Fathonia; Adawiyah Ritonga; Ega Trianingsih Aksana; Siti Salamah Br Ginting (Bilangan : Jurnal Ilmiah Matematika, Kebumian dan Angkasa, 2025)
This research employs a Systematic Literature Review (SLR) approach to analyze the application of the simplex method as a tool for solving real-world optimization problems. Mathematics education plays a crucial role in developing critical thinking and achieving accurate results. Linear programming, with its highly effective simplex method, is a branch of mathematics proven to solve various optimization challenges such as cost minimization, profit maximization, distribution, and scheduling. In practice, the simplex method is an alternative algorithm that systematically searches for the optimal solution to problems by moving from one feasible solution to another until the best result is achieved. This study identifies, examines, evaluates, and interprets relevant studies on the simplex method's application in real-world contexts. Our review of 20 journals reveals that the simplex method is highly effective in solving a wide range of optimization problems, from large-scale industries to Micro, Small, and Medium Enterprises (MSMEs). Examples of its application include optimizing fish feed costs at PT. Indojaya Agrinusa, maximizing profits for Seblak MSMEs, determining optimal sales quantities for areca nuts, and optimizing the production of tofu and pottery crafts, among others. The simplex method's ability to consider various limiting factors has proven to be extremely helpful.